Body fat, metabolic syndrome and hyperglycemia in South Asians - Misra, A.; Soares, Mario; Mohan, V.; Anoop, S.; Abhishek, V.; Vaidya, R.; Pradeepa, R. (2018)
The prevalence of overweight and obesity is escalating in South Asian countries. South Asians display higher total and abdominal obesity at a lower BMI when compared to Whites. Consequently, metabolic dysfunction leading to metabolic syndrome (MetS) and type 2 diabetes mellitus (T2DM) will account for a majority of the health burden of these countries. In this review, we discuss those factors that contribute to MetS and T2DM in South Asians when compared to whites, focusing on adiposity. Abdominal obesity is the single-most important risk factor for MetS and its predisposition to T2DM. Excessive ectopic fat deposition in the liver (non-alcoholic fatty liver disease) has been linked to insulin resistance in Asian Indians, while the effects of ectopic fat accumulation in pancreas and skeletal muscle need more investigation. South Asians also have lower skeletal muscle mass than Whites, and this may contribute to their higher risk T2DM. Lifestyle factors contributing to MetS and T2DM in South Asians include inadequate physical activity and high intakes of refined carbohydrates and saturated fats. These are reflective of the recent but rapid economic transition and urbanization of the South Asian region. There is need to further the research into genetic determinants of dysmetabolism as well as gene x environment interactions. Collectively, MetS and T2DM have multi-factorial antecedents in South Asians and efforts to combat it through low-cost and socio-culturally appropriate lifestyle interventions need to be supported.